Do Environmental Performance and Disclosure Contribute to the Economic Performance? The Moderating Role of Corporate Action - Saputra, Indra; Murwaningsari, Etty (Journal of Accounting Research, Organization and Economics, 2021)
Objective The purpose of this study is to examine the effect of environmental performance and environmental disclosure on economic performance of the Indonesian listed manufacturing companies by using corporate action as a moderating variable. Design/methodology This study used secondary data obtained from the official website of the Indonesia Stock Exchange and the Ministry of Environment and Forestry, Indonesia. The sample consisted of manufacturing companies that are listed and follow the Company Performance Rating Assessment Program (Program Penilaian Peringkat Kinerja Perusahaan/PROPER) issued by the Ministry of Environment and Forestry for the period of 2011-2016. The study employed a purposive sampling approach, which includes 22 companies with 132 observations. The multiple linear regression method was used for data analysis.Results The results indicated that environmental performance has a significant positive effect while environmental disclosure has a significant negative effect on economic performance. The testing of corporate action as a moderating variable demonstrated that it could not strengthen the effect of environmental performance on economic performance. However, it could enhance the effect of environmental disclosure on economic performance.